Evaluation of Bridge Projects in Iraq Using International Performance Evaluation Standards (USAID) - Al-khazrajy, Maryam Gamal Saleem; Al-Zwainy, Faiq M.S.; Mohamed, Sherif; Hayder, Gasim (Al-Nahrain Journal for Engineering Sciences, 2025)
This study evaluates the performance of bridge projects in Iraq using international performance evaluation standards set by USAID. The assessment focuses on two major bridge projects in Baghdad: the Bridge Project over the Army Canal and the Design and Implementation Project for developing the Shaljia and Tobji Intersection. The evaluation standards include relevance, efficiency, effectiveness, impact, and sustainability. Data collected from these projects were analyzed to measure performance against these standards. The results revealed significant gaps between both projects’ expected and actual performance. The Bridge Project over the Army Canal showed moderate performance in relevance and sustainability but had substantial weaknesses in effectiveness. The Shaljia and Tobji, Intersection Development project, exhibited major weaknesses across all standards. The study concludes a critical need for better planning, improved resource utilization, enhanced stakeholder communication, and more effective monitoring and evaluation mechanisms to address these performance gaps and achieve desired project outcomes. These findings highlight the importance of adopting comprehensive and adaptable evaluation standards to improve the efficiency and effectiveness of infrastructure projects in Iraq. The research provides valuable insights for stakeholders involved in bridge projects, emphasizing the need for ongoing improvement in project management practices to ensure infrastructure reliability and safety.